2020
DOI: 10.1177/0042098020916440
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood perceptions and residential mobility

Abstract: This paper considers the ways in which neighbourhood perceptions can differentially affect residential mobility, particularly in low-income areas. Given the long history of understanding the relationship between neighbourhood context and residential mobility, this study includes measures of satisfaction, safety, decay and neighbourly agency to understand mobility. Using data from the Making Connections Initiative, this paper uses a unique panel survey across neighbourhoods in 10 US cities undergoing spatial an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 49 publications
(35 reference statements)
1
14
0
Order By: Relevance
“…A final broad implication of these findings is that individual-level characteristics are associated with neighborhood satisfaction and subsequent mobility in ways that tract-level characteristics (e.g., population size or residential turnover) are not. Consistent with Kasarda and Janowitz (1974) and more recent findings (Jones and Dantzler 2021), my findings suggest that individual-level characteristics and perceptions are stronger predictors of residential mobility than other neighborhood-level factors.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A final broad implication of these findings is that individual-level characteristics are associated with neighborhood satisfaction and subsequent mobility in ways that tract-level characteristics (e.g., population size or residential turnover) are not. Consistent with Kasarda and Janowitz (1974) and more recent findings (Jones and Dantzler 2021), my findings suggest that individual-level characteristics and perceptions are stronger predictors of residential mobility than other neighborhood-level factors.…”
Section: Discussionsupporting
confidence: 89%
“…In this way, personal relationships can be seen as important facilitators of neighborhood satisfaction. As Mesch and Manor (1997:507) identified from the literature, “local social involvement, in particular with friends and kin, is the most consistent and significant cause of attachment to place.” And one common way researchers have operationalized place attachment has focused on people’s perceptions of the quality of their environment, that is, their neighborhood satisfaction (e.g., Jones and Dantzler 2021; Sharp and Warner 2018).…”
Section: Background and Theorymentioning
confidence: 99%
“…Other recent work also highlights the important role of perceptions. For example, Jones & Dantzler (2021) show that perceptions of different neighbourhoods in a city shape residential mobility.…”
Section: Stage Two: Analysis Of the Role Of Perceptionsmentioning
confidence: 99%
“…Perceptions themselves have been shown to be the link between neighborhood structural concerns measured through the census and adolescent outcomes (Plunkett et al, 2007). In a recent study, Jones and Dantzler (2021) found that in the context of residential mobility, perceptions of neighborhoods matter more in moving than the objective neighborhood setting. These findings highlight the importance of actual reported experiences and perceptions of neighborhood rather than assumed exposures with administrative data.…”
Section: Introductionmentioning
confidence: 99%